The Enabling Role of Digital Technology for Rural Revitalization: QCA Study Based on Digitization Index of 58 Counties in Anhui Province - Wu, Ji (International Journal of Global Economics and Management, 2024)
As part of the modernization of the national governance system and governance capacity, the local digital governance model is still in the exploratory stage, and there is an urgent need for academics to clarify whether digital technology can, to a certain extent, empower rural economic development and promote rural revitalization. Taking 58 counties in Anhui Province as the research object, this study adopts a multilevel governance theoretical perspective and the QCA method to identify the realization paths of high digital governance levels. It is found that (1) none of the single antecedent conditions can individually constitute a necessary condition for the improvement of county economic development level (high quality development of county economy). (2) The grouping analysis reveals that there is a common path to promote the improvement of county economic development level, i.e., the digital village grouping consisting of digital infrastructure, digital governance, and digital life. The findings of the study help deepen the rational understanding of the government and localities on digital governance, provide practical insights on digital governance in counties in China, and propose a path to optimize digital empowerment for rural revitalization.